MANAGEMENT OF GAME MEDIA DEVELOPMENT FOR EARLY CHILDHOOD - Firman Ashadi; Muhammad Haris; Didik Cahyono; Yuditia Prameswari; Yunita Dwi Wikandari (Jurnal Scientia, 2023)
The objective of this study is to examine the implementation approach employed in the management of Game Media Development for Early Childhood. This study employs the literature review methodology to consolidate data and analyze findings from many literature sources, with the aim of constructing a thorough comprehension of optimal practices and methods in the management of game media creation for early childhood. The findings indicate that an effective strategy for developing educational games for children involves incorporating educational components within the game in an engaging manner. The inclusion of game content that aligns with positive values and receives parental approval is a critical determinant in establishing a favorable play environment. By implementing these tactics, play can serve as a valuable instrument in facilitating early childhood learning and development in an enjoyable and gratifying manner.